Harriet Taylor Mill - Seiz, Janet A; Pujol, Michèle A (American Economic Review, 2000)
While Harriet Taylor Mill's work on feminist economics has only recently begun to receive the attention it deserves, one can hardly say that she was earlier ignored: for more than a century, debate has raged over the extent and nature of her influence on John Stuart Mill. The debate was provoked by Mill himself, who used quite extravagant language in describing his wife and her contributions to his work.1 The following example is from his Autobiography (J. S. Mill, 1873 [1965 p. 251]), completed after Harriet's death and published only after his own: